2004
DOI: 10.1080/00087114.2004.10589418
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation and evolution in some species ofDalbergiaLinn.f. (Fabaceae)

Abstract: The present study deals with the extent of genome size variation and evolution in some species of Dalbergia. The interspecific 4C DNA content variation has been analyzed in 30 accessions belonging to ten species of Dalbergia. The 4C DNA content in ten Dalbergia species ranges from 5.85 pg in D. lanceolaria to 7.88 pg in D. horrida, about 1.3 fold variation is apparent at a constant chromosome number 2n=2x=20. ANOVA test reveals significant variation between species. Like other woody angiospermic taxa, tree spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Ten diploid (2n = 20) species of Dalbergia show a 1.3fold variation in 4C DNA contents from 5.85 pg D. lanceolaria to 7.88 pg in D. horrida. While the tree species show a range from 5.85 pg in D. lanceolaria to 7.22 pg in D. sissoides the shrubby and climber species included in the sample show a much narrow but higher range from 7.36 pg in D. rubiginosa to 7.88 pg in D. horrida (HIREMATH and NAGASAMPIGE, 2004). In Lonchocarpus 51 diploid (2n = 22) taxa including 42 species show 4C DNA values ranging from 1.92 pg in L. santarosanus to 2.86 in L. xuul depicting a 1.49-fold difference, which does not show any correlation with altitude (PALOMINO and SOUSA, 2000).…”
Section: Genome Size Variation At Homoploid Level and By Polyploidymentioning
confidence: 87%
“…Ten diploid (2n = 20) species of Dalbergia show a 1.3fold variation in 4C DNA contents from 5.85 pg D. lanceolaria to 7.88 pg in D. horrida. While the tree species show a range from 5.85 pg in D. lanceolaria to 7.22 pg in D. sissoides the shrubby and climber species included in the sample show a much narrow but higher range from 7.36 pg in D. rubiginosa to 7.88 pg in D. horrida (HIREMATH and NAGASAMPIGE, 2004). In Lonchocarpus 51 diploid (2n = 22) taxa including 42 species show 4C DNA values ranging from 1.92 pg in L. santarosanus to 2.86 in L. xuul depicting a 1.49-fold difference, which does not show any correlation with altitude (PALOMINO and SOUSA, 2000).…”
Section: Genome Size Variation At Homoploid Level and By Polyploidymentioning
confidence: 87%
“…lanceolaria and D . paniculata were closely related [ 15 ]. These observations indicated that matK , nrITS , rbcL and matK+rbcL could correctly identify the reported relationships among the Dalbergia species and hence, they could most likely be successful as barcodes for this genus.…”
Section: Resultsmentioning
confidence: 99%
“…It is confined to the tropical regions of the world with Amazonia, Madagascar, Africa and Indonesia as the centers of diversity [ 13 , 14 ]. About 200 species comprise the genus, of which nearly 35 are found in India with 10–15 species in the Western Ghats (WG) alone [ 14 , 15 ]. The overall species diversity is high in WG Seven species are endemic to this region ( http://wgbis.ces.iisc.ernet.in/biodiversity/sahyadri_enews/newsletter/issue38/article/index.htm ); hence, we choose to select WG as our study area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations